Testosterone Relaxes Isolated Human Radial Artery by Potassium Channel Opening Action - Melik Seyrek; Oguzhan Yildiz; Hasan Basri Ulusoy; Vedat Yildirim (Elsevier, 2007)
Preliminary clinical studies of testosterone therapy in male patients with coronary artery disease obtained promising results. However, little is known about the in vitro effects of testosterone in human isolated arteries. We investigated the effect of testosterone on contractile tone of human isolated radial artery (RA). Testosterone was added (0.1 - 300 µM ) cumulatively to organ baths after precontraction with KCl (45 mM) and phenylephrine (PE, 10 µM). Testosterone-induced relaxations were tested in the presence of the cyclooxygenase inhibitor indomethacin (10 µM), nitric oxide synthase inhibitor Nω-nitro-L-arginine methyl ester (L-NAME, 100 µM), non-selective large conductance Ca2+-activated and voltage-sensitive K+ channel inhibitor tetraethylammonium (TEA, 1 mM), ATP-sensitive K+ channel inhibitor glibenclamide (GLI, 10 µM), and voltage-sensitive K+ channel inhibitor 4-aminopyridine (4-AP, 1 mM). Testosterone produced relaxation in human RA (Emax: 53.03 ± 2.76% and 66.83 ± 1.97% of KCl and PE-induced contraction, respectively). Except for GLI, the relaxation to testosterone is affected by neither K+ channel inhibitors (TEA, BaCl2, and 4-AP), L-NAME, nor indomethacin. We report for the first time that supraphysiological concentrations of testosterone induces relaxation in RA. This response may occur in part via ATP-sensitive K+ channel opening action. Keywords:: human radial artery, testosterone, vasodilation, potassium channel